Optical fiber communications planning with the use of fascal probability for forecasting traffic limitation - Neittanit, S.; Leepila, R.; Sudkaewd, S.; Noppanaiteepoug, S.; Kliawne, A. (My University, 2003)
The objective of this paper is to improve tlrc calculation method of WDM traffic in optical fiber network. At present, the requirement of traffic is random even and the problem of lhe planned engineenhg is to make the flexible model to be stood data for planning and developing the existing optical communication network system. The most of appropriate models of the optical fiber network, therefore, should be able to reproduce the aforesaid type and the quantity of applicable graphic. Thc inodel should be suitable for the presentation of Pascal Distribution because it will be a new alternative for planning of communication network that is able to adjust the value to quantities of wavelength graphics by the analysis of the b a f h limitation probability that i s to compare the Poisson distribution with wavelength converter in order to improve the system performance.